2020
DOI: 10.1142/s2424835520500101
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy Comparison of Hyaluronic Acid and Corticosteroid Injection in Treatment of Trigger Digits: A Randomized Controlled Trial

Abstract: Background: Although the current nonsurgical treatment for trigger digits is corticosteroid (CS) injection, it often comes with adverse effects that may cause some limitations. Currently, Hyaluronic acid (HA) has been successfully used in tendinopathy and may be used in stenosing tenosynovitis. The aim of this study is to compare the efficacy of ultrasound-guided injection between the HA and CS in trigger digits treatment. Methods: Double-blind randomized controlled trial was conducted. Fifty patients with 66… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…Injection therapy was associated with a shorter recovery time, with a consequent reduced absence from sports and work activities and fewer complications (52). In accordance, other Authors found that HA achieved similar effect as steroid injection in trigger finger with a long-lasting functional improvement (MHQ scores continued to increase in the HA group at 3 months follow-up) without adverse events, until 6 months of follow-up (53,54). Orlandi et al compared the 6 months outcome of three different ultrasound guided percutaneous injection treatment for de Quervain's disease (steroid alone, steroid with saline, steroid with HA).…”
Section: Tenosynovitissupporting
confidence: 54%
“…Injection therapy was associated with a shorter recovery time, with a consequent reduced absence from sports and work activities and fewer complications (52). In accordance, other Authors found that HA achieved similar effect as steroid injection in trigger finger with a long-lasting functional improvement (MHQ scores continued to increase in the HA group at 3 months follow-up) without adverse events, until 6 months of follow-up (53,54). Orlandi et al compared the 6 months outcome of three different ultrasound guided percutaneous injection treatment for de Quervain's disease (steroid alone, steroid with saline, steroid with HA).…”
Section: Tenosynovitissupporting
confidence: 54%
“…After systematic review, 24 articles met the inclusion criteria. 5,6,9,10,[14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] Among them, 8 of them were excluded from our meta-analysis (Supplemental Appendix B) and 16 of them (including 1185 patients) which reported success were included in our meta-analysis ( Figure 1). 5,6,9,10,[14][15][16][17][18][19][20][21][22][23][24][25] The main characteristics of the included articles are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…The authors noted that both LMW-HA and corticosteroids provide a comparable therapeutic effect in the medium term. However, it is necessary to consider that corticosteroids have a cytotoxic effect on tendons [ 51 ].…”
Section: Resultsmentioning
confidence: 99%